O conceito de somação e os termos nomeadores de indivíduos, no artigo identidade, ostensão e hipóstase, de Quine - Xavier, Caio Bismarck Silva (2023)
The general goal of this dissertation is to explain the influence of the concept of “summation”, that came from the nominalist work developed by Quine together with Goodman, in the way in which Quine proposes to discuss the identity and the role of general and singular terms in the article Identity, ostension and hypostasis (1950). Our dissertation aims to show that in this article, Quine suggests a critique of the distinction between singular terms and general terms based on the concept of “summation”. Our hypothesis is that the philosopher would consider that this distinction could be set aside, if the conception of language as a theory of reference were replaced by another conception that used, in place of the concept of “reference”, the concept of “summation”. In the course of our argument, we will try to show what Quine can and what he cannot recover concerning the conception of language as a theory of reference using only the concept of “summation” and an act of ostension, linguistically represented by the demonstrative pronoun.